Interrelationship Between Health Insurance Status and Prostate Cancer Grade Can Have Critical Impact on Prostate Cancer Disease Control: A Retrospective Cohort Study. (29th March 2019) - Awasthi, Shivanshu; Gerke, Travis; Williams, Vonetta L.; Asamoah, Francis; Fink, Angelina K.; Balkrishnan, Rajesh; Park, Jong Y.; Yamoah, Kosj
The extent to which prostate cancer (PCa) pathology interacts with health insurance to predict PCa outcomes remains unclear. This study will assess the overall association of health insurance on PCa disease control and analyze its interrelationship PCa pathology. A total of 674 PCa patients, treated with prostatectomy from 1987 to 2015, were included in the study. Freedom from biochemical failure (FFbF) was used as a measure of PCa disease control. Methods of categorical and survival analysis were used to analyze the relationships between health insurance, PCa pathology, and FFbF. A total of 63.3% patients were privately insured, 27.1% were publicly insured, and 9.5% were uninsured. In a multivariable model, privately (hazard ratio [HR] = 0.64, 95% confidence interval [CI]: 0.42-0.97, P = .03) and publicly (HR = 0.65, 95% CI: 0.41-1.04, P = .07) insured patients showed improvement in FFbF compared to uninsured patients. The association of health insurance was significantly stronger for the patients with pathologically low grade PCa (pathologic Gleason Score 3+3 & preoperative prostate-specific antigen ≤10 ng/mL), likelihood ratio P = .009. Privately (HR = 0.22, 95% CI: 0.10-0.46) or publicly (HR = 0.26, 95% CI: 0.11-0.60) insured patients with low grade PCa demonstrated favorable association with FFbF. Patients with private and public insurance were more likely to experience favorable treatment. The association of health insurance on PCa disease control is significantly stronger among patients with pathologically low grade PCa. This study identifies health insurance status as pretreatment surrogate for PCa disease control.